Your story, our story: the transformative power of life narratives. Issue 6 (1st November 2020) - Welch, Marguerite A.; Saunders, Akasha, Aka Pete; Buergelt, Petra T.; Gilpin-Jackson, Yabome; Ferguson, Janet; Marsick, Victoria J.
ABSTRACT: The stories in this article opened the 2018 International Transformative Learning (TL) Conference. Mezirow founded this conference to grow living theory, but over time, paradoxically, allegiance to his framing of TL can be seen as limiting growth. The Conference designers invited participation from new geographical, cultural, social and political perspectives to bring forward unheard voices to create bridges among differences. Framed by the imaginal and holistic approaches to TL, this article shares the personal stories of transformation narrated by five panelists and the 'wicked' questions these stories evoked. The authors reflect on the humanizing, heart-ful space that sharing stories created, which re-minded those present of shared community. TL is about change in the individual, as theory seeks to explain; yet it is also about embedded social, cultural norms and assumptions that shape and sustain systems. The authors conclude by reflecting on the humanizing potential of narrative, as well as the theorizing about the interdependence between individual and systemic transformation.